1996
DOI: 10.1038/382090a0
|View full text |Cite
|
Sign up to set email alerts
|

A helical arch allowing single-stranded DNA to thread through T5 5'-exonuclease

Abstract: THE 5'-exonucleases are enzymes that are essential for DNA replication and repair. As well as their exonucleolytic action, removing nucleotides from the 5'-end of nucleic acid molecules such as Okazaki fragments, many 5'-3'-exonucleases have been shown to possess endonucleolytic activities. T5 5'-3'-exonuclease shares many similarities with the amino terminal of eubacterial DNA polymerases, although, unlike eubacteria, phages such as T5, T4 and T7 express polymerase and 5'-exonuclease proteins from separate ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
234
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(237 citation statements)
references
References 21 publications
3
234
0
Order By: Relevance
“…Comparison of the results obtained with Ps-Y and 5OVH substrates sheds light on the likely structure of the protein-DNA complex. The original DNA-binding model presented for T5 5Ј nuclease (8) is not fully compatible with the results of the quantitative binding assays presented herein. We propose a model for flap endonuclease-DNA interaction.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Comparison of the results obtained with Ps-Y and 5OVH substrates sheds light on the likely structure of the protein-DNA complex. The original DNA-binding model presented for T5 5Ј nuclease (8) is not fully compatible with the results of the quantitative binding assays presented herein. We propose a model for flap endonuclease-DNA interaction.…”
mentioning
confidence: 85%
“…The most variable region seems to be that comprising a helical arch in T5 5Ј nuclease, the observation of which led us to develop a model of substrate binding (ref. 8; Fig. 2).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…These 5Ј-nucleases are either physically linked to polymerases as in Taq polymerase and E. coli polymerase I or exist as subunits within complexes that contain discrete polymerase and nuclease activities. Examples of this latter group include the phage-encoded T5 5Ј-nucleases (4,5), archaeal (6) and mammalian flap endonuclease I (7), all of which share an ␣/␤ topology with a common central ␤-sheet and similar surrounding ␣-helices. The active site comprises a cleft formed within the central ␤-sheet; at the bottom of cleft is a set of conserved acidic residues that are essential for binding the three divalent metal ions (two Mn 2ϩ ions and one Zn 2ϩ ion) required for nuclease activity.…”
mentioning
confidence: 99%
“…A first glance of the salient features of the active site of XPG was provided by crystal structures of the exonuclease domains of T4 RNase H and T5 5'-exonuclease. 19,20 These studies showed a number of conserved acidic residues that coordinate metal ions. Sequence alignments of XPG with these structures revealed that several conserved acidic residues, including Glu77, Glu791 and Asp812, are poised to be part of the active site.…”
Section: Discovery and Cloning Of Xpgmentioning
confidence: 99%